THE IMPACT OF BIG DATA ANALYTICS ON IMPROVING FINANCIAL REPORTING QUALITY - Nagat Mohamed Marie Younis (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Purpose – The current study aims to clarify the importance of big data analytics and its role in changing the accounting profession and the roles of accountants, in addition to testing the impact of big data analytics on improving financial reporting quality in the Saudi environment. Design/ methodology/ approach – To achieve the study's goals and validate hypotheses, relevant previous literature and research are referred. Also, a field study is conducted by distributing a questionnaire of (154) individual academics, financial analysts, accountants, and experts in the field of analyzing big data in the Kingdom of Saudi in 2019. Data are analyzed by using the program of Statistical Package for Social Science (SPSS 17.0). Findings – The study concluded that although business organizations face several challenges when analyzing data, big data analytics has a significant role in achieving high competitiveness for institutions, improving the accounting information quality, providing appropriate information that helps in rationalizing decisions within the economic unit, and providing future information affecting stakeholder's decisions. The study also has proved that there is a statistically significant effect of big data analytics on improving the quality of accounting information, as big data analytics clearly affects the characteristics of the accounting information quality, positively affecting the quality of financial reports. Originality/ Value – Originality/ Value – The analytics of big data is one of the most important topics where it positively affects the improvement of accounting information quality, which reflects on financial reporting quality. Hence, academics and institutions should pay attention to this topic and follow their new ideas. The present study is one of the first studies that deal with this topic and examine the relationship between big data analytics and the characteristics of accounting information which positively affecting financial reporting quality.